2015
DOI: 10.11648/j.ajep.20150401.12
|View full text |Cite
|
Sign up to set email alerts
|

Germination and Root Nodule Formation of Soybean (Glycine max (L.) Merr.) in Ridomil and Chlorpyriphos Treated Soil

Abstract: Germination and root nodule formation of soybean (Glycine max) was evaluated in soil treated with Ridomil (R), Chlorpyriphos (CH), and a Combination of both (COM); using a completely randomized design, and a 3×3 factorial arrangement. Factor 1 was the pesticide type with 3 levels-R, CH, and COM; while factor 2 was the contamination rate (v/wt) with 3 levels-0% (control), 2%, and 4%. Aqueous pesticides preparations (as recommended by manufacturers) were applied once, before seeds were planted. More than Ridomil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It has also been reported to exert detrimental effect on the root biomass, root appearance and disappearance, and root density (Dawson et al 2003;Singh et al 2003a). Even though it did not affect the in vitro growth of Rhizobium, reduced nodulation (Bassey et al 2015) and nitrogen fixation (C 2 H 2 reduction) were observed in alfalfa sweet clover and red clover associated with the application of chlorpyrifos (Smith et al 1978;Parween et al 2011). The Pesticide Action Network (PAN) toxicity study data give a clear picture of severity of accumulation and population, biochemical, and physiological effects of chlorpyrifos in various aquatic plants (Kegley et al 2014).…”
Section: Toxicity On Plantsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has also been reported to exert detrimental effect on the root biomass, root appearance and disappearance, and root density (Dawson et al 2003;Singh et al 2003a). Even though it did not affect the in vitro growth of Rhizobium, reduced nodulation (Bassey et al 2015) and nitrogen fixation (C 2 H 2 reduction) were observed in alfalfa sweet clover and red clover associated with the application of chlorpyrifos (Smith et al 1978;Parween et al 2011). The Pesticide Action Network (PAN) toxicity study data give a clear picture of severity of accumulation and population, biochemical, and physiological effects of chlorpyrifos in various aquatic plants (Kegley et al 2014).…”
Section: Toxicity On Plantsmentioning
confidence: 97%
“…The effects were assessed based on changes in germination pattern, morphological traits (root and shoot length, fresh and dry weight of roots and shoots), biochemical functions, and metabolism. Chlorpyrifos was found to have inhibitory effect on germination in Pinus halepensis seeds and seedlings (Olofinboba and Kozlowski 1982), annual grass and annual forb (Gange et al 1992), ryegrass (Lolium multiflorum) (Korade and Fulekar 2009), different vegetables (Zhang et al 2013), Cenchrus setigerus and Pennisetum pedicellatum (Dubey and Fulekar 2011), white mustard (Sinapis alba L.), maize (Zea mays L.) (Gvozdenac et al 2013), and soybean (Glycine max) (Bassey et al 2015). The intensity of toxicity on seed germination energy, seed germination, survival, and subsequent growth increases with chlorpyrifos concentration (Dubey and Fulekar 2011;Gvozdenac et al 2013).…”
Section: Toxicity On Plantsmentioning
confidence: 99%
“…Chlorpyrifos is toxic to soil microorganisms (Dutta et al, 2010;Orts et al, 2017), plants (Bassey et al, 2015), aquatic system (Ali et al, 2009;Costa et al, 2015;Bonifacio et al, 2017) and even to the higher vertebrates (Sandal and Yilmaz, 2011;Wang et al, 2012;Ojha et al, 2013). Recently, Tiwari et al (2019) highlighted that chlorpyrifos could alter the activity of acetylcholinesterase (AChE), oxidative stress related enzymes, lipid peroxidation (LPO), glutathione content and glutathione S-transferase (GST) activity in Eudrilus eugeniae.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorpyrifos is toxic to soil microorganisms (Dutta et al, 2010;Orts et al, 2017), plants (Bassey et al, 2015), aquatic system (Ali et al, 2009;Costa et al, 2015;Bonifacio et al, 2017) and even to the higher vertebrates (Sandal and Yilmaz, 2011;Wang et al, 2012;Ojha et al, 2013). Recently, García-Gómez et al…”
Section: Introductionmentioning
confidence: 99%